Effects of regulator of G protein signaling 2 (RGS2) overexpression in the paraventricular nucleus on blood pressure in rats with angiotensin II-induced hypertension - Boomer, Shane H.; Liu, Xuefei; Zheng, Hong (Frontiers in Physiology, 2024)
The hypothalamic paraventricular nucleus (PVN) regulates sympathetic activity and blood pressure. The regulator of G protein signaling 2 (RGS2) is a negative G protein regulator, which selectively regulates G⍺q signaling, a potential cause of hypertension. This study aimed to examine angiotensin II (ANG II)-G protein-RGS2 signaling on the central mechanisms of blood pressure control, sympathetic activation, and kidney function. The Sprague Dawley rats were infused with ANG II (200 ng/kg/min) via osmotic mini pump to induce hypertension. Adenovirus (AV) vectors encoding RGS2 was transfected into the PVN in vivo. By radio telemetry measurements, we found AV-RGS2 transfection to the PVN significantly attenuated the increase of mean arterial pressure in ANG II infusion rats from days 2–7 of the 2-week experiment (Day 7: ANG II + AV-RGS2 141.3 ± 10.0 mmHg vs. ANG II 166.9 ± 9.3 mmHg, p < 0.05). AV-RGS2 transfection significantly reduced the serum norepinephrine level and acute volume reflex and increased daily urine volume and sodium excretion in ANG II-infused hypertensive rats. AV-RGS2 transfection significantly reduced G⍺q and PKC protein expressions within the PVN in ANG II infusion rats. In cultured mouse hypothalamic cells, real-time PCR study showed ANG II treatment increased mRNA expression of G⍺q, G⍺s, and RGS2, and AV-RGS2 treatment decreased ANG II-induced mRNA expression of G⍺q and G⍺s. Using confocal imagery, we found that AV-RGS2 attenuated the increase of calcium influx in ANG II-treated cells. Our results suggest that central overexpression of RGS2 in the PVN attenuated the increase of blood pressure and sympathetic outflow, and improves kidney excretory function in hypertensive rats. This may be via the alteration of ANG II-G-protein-RGS2 signaling in the central nervous system.